2016
DOI: 10.3390/w8080358
|View full text |Cite
|
Sign up to set email alerts
|

Heavy Metal Contamination in the Surface Layer of Bottom Sediments in a Flow-Through Lake: A Case Study of Lake Symsar in Northern Poland

Abstract: River-lake systems most often behave as hydrographic units, which undergo complex interactions, especially in the contact zone. One such interaction pertains to the role of a river in the dispersal of trace elements carried into and out of a lake. In this study, we aimed to assess the impact of rivers on the accumulation of heavy metals in bottom sediments of natural lakes comprised in postglacial river-lake systems. The results showed that a river flowing through a lake is a key factor responsible for the inp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
54
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(60 citation statements)
references
References 32 publications
6
54
0
Order By: Relevance
“…Finally, the impact was assessed of rivers on the accumulation of heavy metals in bottom sediments of natural lakes comprised in postglacial river-lake systems [36]. The results obtained showed that a river flowing through a lake is a key factor determining the input/accumulation of the majority of the occurring fractions of heavy metals (Zn, Mn, Cd, and Ni).…”
Section: Effects Of Other Stressorsmentioning
confidence: 99%
“…Finally, the impact was assessed of rivers on the accumulation of heavy metals in bottom sediments of natural lakes comprised in postglacial river-lake systems [36]. The results obtained showed that a river flowing through a lake is a key factor determining the input/accumulation of the majority of the occurring fractions of heavy metals (Zn, Mn, Cd, and Ni).…”
Section: Effects Of Other Stressorsmentioning
confidence: 99%
“…The last years have shown a trend of enhancement in pollution by heavy metals present in the sediments of surface water [8,14]. In this context, the distribution pattern of contaminants across the water column could provide some useful information on the environmetal characteristics of heavy metals such as their transformation and migration [9].…”
Section: Anual Variation Of Metalsmentioning
confidence: 99%
“…Fe, for example, prevents anaemia, and Zn is a cofactor in over 100 enzyme reactions [7]. In the aquatic environment, metals undergo chemical and biogeochemical processes that control their solubility, mobility, bioavailability and toxicity [14]. It is important to know the distribution of contaminants in lake water because it provides information about their origin, transformation and migration that are useful in water reservoir management [9,[15][16].…”
Section: Introductionmentioning
confidence: 99%
“…They cause the environmental pollution from sources such as industrial effluents, mine tailings, land application of fertilizers, atmospheric deposition and leaching of metal ions from the soil into lakes and rivers by acid rain [1][2][3]. The authors of many papers report the impact of heavy metals on aquatic communities including bottom sediments of rivers and lakes [4][5][6][7][8][9]. Numerous natural and anthropogenic factors affect the chemical composition of surface water sediments [10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Numerous natural and anthropogenic factors affect the chemical composition of surface water sediments [10][11][12]. In the case of flow-through lakes often the most important material is the suspended and dissolved one, transported by supplying river, especially passing through urban, rural or agricultural areas [9]. The composition of sediments depends on geological structures, geomorphology and weathering process, so the background values of individual compounds are characteristic for each region.…”
Section: Introductionmentioning
confidence: 99%